2020
DOI: 10.1002/gepi.22294
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate confounding in trio relationships: The importance of complete data in effect size estimation

Abstract: We present an important characteristic of trio models which may lead to bias and loss of power when one parent is unmodeled in trio analyses. Motivated by recent interest in estimating parental effects on postnatal and later-life phenotypes, we consider a causal model where each parent has both an effect on their child's phenotype which is mediated through the genotype transmitted to the child and a direct effect on the phenotype through the parentally provided environment. We derive the power and bias of mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Second, the magnitude of genetic nurture effects was slightly smaller in the virtual parent design versus the statistical control approach. A recent study has shown the importance of using complete trio data, as missing the genotype of one parent can bias direct genetic effects and genetic nurture effects (Tubbs, Zhang, & Sham, 2020). Evidence from one of the included studies (T. Morris et al, 2020) using both partial and full statistical control approach echoed this view.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the magnitude of genetic nurture effects was slightly smaller in the virtual parent design versus the statistical control approach. A recent study has shown the importance of using complete trio data, as missing the genotype of one parent can bias direct genetic effects and genetic nurture effects (Tubbs, Zhang, & Sham, 2020). Evidence from one of the included studies (T. Morris et al, 2020) using both partial and full statistical control approach echoed this view.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the correlation between parental and offspring genotypes, GWAS captures both the direct and indirect genetic effects in its estimates, which further complicates the interpretation of GWAS results (13). If the genetic nurture effect (i.e., parental genotypes affecting offspring phenotype) is present for a given trait, downstream analyses based on GWAS associations could be biased and misleading (6,8,27).…”
mentioning
confidence: 99%
“…For example, bias amplification has already been recognized in the propensity score literature [12, 13], where the inclusion of instrumental variables (Z) in a propensity score in the presence of unmeasured confounding leads to bias amplification (sometimes referred to as Z-bias [15, 20]). Furthermore, bias amplification is the same phenomenon that leads to bias in within-family/trio mendelian randomization when one parent’s genotypes are omitted [26]. It is also bias amplification that gives rise to inflation of non-shared confounding in sibling analyses [16, 27].…”
Section: Discussionmentioning
confidence: 99%